New species of Termitomyces (Agaricales, Lyophyllaceae) from Yunnan Province, China - Ao, Cheng-Ce; Mu, Li-Dan; Luo, Hong-Mei; Tang, Song-Ming; Zhao, Long; Ye, Yang; Luo, Zong-Long; Li, Shu-Hong (Phytotaxa, 2025)
Termitomyces species are the preferred food of Chinese consumers because of their unique taste, and this genus is only distributed in Asia and Africa. In this paper, a new species of T. nigroalbus from Yunnan, China, is introduced and described, which is morphologically characterized by a black-gray surface of the pileus, pale gray perforatorium, frequent cleavage toward the margin, cylindrical stipe, pale gray on the surface, abundant pale gray squamulose on the surface, absent annulus, and white pseudorrhiza. A phylogenetic tree established using nrLSU and mtSSU showed that T. nigroalbus is distinct from other known Termitomyces species. Comprehensive descriptions, color photographs, and a phylogenetic tree showing the position of the new species are provided.